ANALISIS STRATEGI PEDAGANG KULINER DITINJAU DARI PERENCANAAN KEUANGAN DAN KONDISI SOSIAL EKONOMI KELUARGA DI KACAMATAN BINAMU KABUPATEN JENEPONTO - RAHUL; THAMRIN TAHIR; MUHAMMAD HASAN; MUHAMMAD DINAR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
The purpose of this study is to determine the methods culinary traders utilize to increase their revenue for family welfare as well as the challenges they encounter in doing so. Using a descriptive qualitative methodology, this study. Using data analysis methods including data reduction, data collecting, data presentation, and conclusion-drawing in this study According to the study's findings, culinary traders maintain product quality, set reasonable product prices, run promotions, select locations strategically, and offer the best service possible to customers. On the other hand, they face challenges like business location restrictions and venture capital constraints. Data analysis was done using SWOT analysis.